PERAN YPKP SEBAGAI KELOMPOK KEPENTINGAN (INTEREST GROUP) DALAM MEMERJUANGKAN HAK HAK KORBAN PERISTIWA G30S (Studi Kasus Aktivitas YPKP di Kabupaten Pati) - Adipta Wisnu Wardhani (Program Magister Ilmu Politik, Universitas Diponegoro, 2017)
Indonesia is one of the countries that embraced democracy in system administration. Indonesia has proved it by holding presidential and vice presidential election directly. Besides the Indonesian people freely organizing meetings and talking freely to express opinions, criticism, or even overseeing the governance system. Freedom of religion is a manifestation of the democratic state.The dynamics of the Non-Governmental Organization (NGO) was born along with the birth of a new order of the early 1970s. The birth of this order to the economic development paradigm and focusing on economic growth, had an impact on short-term plans, medium and long-national development, which is implemented in the five year plan. NGO as a partner of government to accelerate the process of national development in all fields.This research will be directed to find out how YPKP activity as well as how the interaction / relationship dynamics YPKP with the Government. Murder Victims Research Foundation 1965/1966 (YPKP 65) is the organization's first victim in Indonesia fighting for the enforcement of human rights on Human Tragedy 1965/1966. YPKP 65 judging cases of crimes against humanity 1965/1966 has not been seriously considered in law and politics of the country. During the 12 years of reform, none of the political elite, both in Parliament and in the executive, even in the judiciary investigate cases in 1965.After analysis, it appears that YPKP 65 Pati Regency consolidate internally and externally by holding regular meetings so that the communication that exists among members of intertwined smoothly, as did the communications against similar organizations lainnya.YPKP 65 Pati regency using communication media / communication channels that are electronically for obtain information related to the organization's objectives. There was also the dynamics between YPKP with another NGO. Keywords: Role, Interest Groups, Dynamics.